Development and Suggestion of a Cardiac CTA Scoring System for the Prediction of Revascularization Success in Chronic Total Occlusions (CTO) of the Coronary Arteries - Roller, F. C.; Harth, S.; Rixe, J.; Krombach, G. A.; Schneider, C. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Objective: Analyzing occluded segments with computed tomography angiography (CTA) prior to percutaneous coronary intervention (PCI) increased revascularization success in chronic total occlusions (CTO). The aim of our study was to develop a scoring system for the prediction of PCI success in CTO.Materials and Methods: 41 consecutive CTO patients (30 male; 63.1 years +/– 8.3 standard deviation) underwent CTA prior to PCI. All CTOs were categorized by two radiologists in consensus regarding the presence of special features and without knowledge of PCI outcome. All outcome criteria were evaluated. Afterwards one point was assigned for each unequally distributed outcome criteria per CTO and all points were added up to a single score.Results: Severe calcifications (failure group 68.8 % vs. success group 28.0 %; p < 0.02) and intraluminal calcifications (68.8 %; 40.0 %), tortuosity (25.0 %; 0 %; p < 0.02), linear intrathrombus enhancement (37.5 %; 60.0 %) and distal vessel disease (68.8 %; 44.0 %) were unequally distributed. By adopting a threshold of 4 points or higher (maximum 5 points), the results were: sensitivity 31.3 %, specificity 100 %, negative predictive value (NPV) 69.4 % and positive predictive value (PPV) 100 %. The PCI complication rate was 9.8 % and the mean contrast media amount was 234.4 ml.Conclusion: With the suggested scoring system, based on five CTA criteria, PCI failure could be predicted with high PPV and specificity in our group of patients, but the NPV and sensitivity are low. However, 5 unsuccessful PCIs (13.2 %) could have been avoided and none would have been wrongly omitted. Regarding the complication rate during PCI and the high amounts of contrast media needed, a prediction system appears to be desirable and should be the object of large-scale trials.Key points:• Single predictors of revascularization success in CTO have been identified.• Success rates are improved by analyzing CTA data sets prior to revascularization approaches.• Prediction of revascularization success via a scoring system based on five CTA criteria seems promising.• Patient selection for the right treatment options might be improved in the future due to application of the scoring system.• Also risks, complications, contrast media amounts and radiation doses might be reduced.Citation Format:• Roller FC, Harth S, Rixe J et al. Development and Suggestion of a Cardiac CTA Scoring System for the Prediction of Revascularization Success in Chronic Total Occlusions (CTO) of the Coronary Arteries. Fortschr Röntgenstr 2016; 188: 172 – 178
Keywords: cardiac; heart; angiography; interventional procedures; CT angiography